Depression among unaccompanied minor refugees: the relative contribution of general and acculturation-specific daily hassles. Issue 3 (3rd May 2016) - Keles, Serap; Friborg, Oddgeir; Idsøe, Thormod; Sirin, Selcuk; Oppedal, Brit
ABSTRACT: Objectives . This study is designed to provide an empirical conceptualization of daily hassles among unaccompanied refugees, and whether they might affect mental health of young refugees after resettlement. First, we examined the underlying structure of daily hassles conceptualized as measuring general and acculturation-specific hassles. Second, we examined whether these two distinct categories of daily hassles significantly contribute to depression above and beyond the impact of premigration trauma. Design . The study was based on self-report questionnaire data collected from 895 unaccompanied refugees who had been granted residence in Norway. Results . Using structural equation modeling, the results confirmed the grouping of hassles in two general categories, which explained 43% of the variance in depression. Conclusion . The findings underscore the importance of current life conditions for unaccompanied refugees' mental health.